Quantification of stimulus-evoked tactile allodynia in free moving mice by the chainmail sensitivity test - Ozdemir, Yildirim; Nakamoto, Kazuo; Boivin, Bruno; Bullock, Daniel; Andrews, Nick A.; González-Cano, Rafael; Costigan, Michael (Frontiers in Pharmacology, 2024)
Chronic pain occurs at epidemic levels throughout the population. Hypersensitivity to touch, is a cardinal symptom of chronic pain. Despite dedicated research for over a century, quantifying this hypersensitivity has remained impossible at scale. To address these issues, we developed the Chainmail Sensitivity Test (CST). Our results show that control mice spend significantly more time on the chainmail portion of the device than mice subject to neuropathy. Treatment with gabapentin abolishes this difference. CST-derived data correlate well with von Frey measurements and quantify hypersensitivity due to inflammation. Our study demonstrates the potential of the CST as a standardized tool for assessing mechanical hypersensitivity in mice with minimal operator input.